A cross sectional study of hypertension and their risk factors in fishermen of Chennai district - Muthukrishnan, Gopal; Pillai Uma, Suresh Balan Kumaraswamy; V., Anantharaman V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is one of the major public health issues in worldwide. The objective of this study was to find out the prevalence of hypertension and its associated risk factors in fishermen of Chennai district, Tamil Nadu, India. Methods: The cross sectional study was conducted among 519 fishermen at the coastal areas of north Chennai district selected by multistage cluster sampling method. Results: In our present study, the significantly associated with the factors included age, level of education, economic status, marital status, BMI, diabetes mellitus, diet, smoking and alcohol user were significantly association (p<0.05) with hypertension. The study included 519 fishermen. Among them, 63% (328) were in the age group of 36–55 years, 24% (124) were in the age group of 18-35 years, 13% (67) were >55 years. The fishermen population showed a prevalence of 46.6% for hypertension. The prevalence of smoking tobacco use and alcohol use were found 34.30% and 71.68%. The average SBP and DBP was 127 and 84 mmHg respectively. The mean BMI was 24 (4.38) kg/m2. The prevalence of hypertension was found in 45% and 38.73% were having abdominal obesity. Conclusions: The prevalence of hypertension was higher than the general population. The present study showed a significant association between the duration of alcohol use and prevalence of hypertension although smoking was not found to have significant association. The present study supports the association of obesity with hypertension.